Force acquisition frequency is less impaired compared to grip strength or hand dexterity in individuals with chronic stroke - Quentin Sanders; Vicky Chan; Oliver Stoller; David Reinkensmeyer (Experimental Brain Research, 2022)

Plant removal across an elevational gradient marginally reduces rates, substantially reduces variation in mineralization - Kenna E. Rewcastle; Jeremiah A. Henning; Quentin D. Read; Rebecca E. Irwin; Nathan J. Sanders; Aimée T. Classen (Ecology, 2022)
The loss of aboveground plant diversity alters belowground ecosystem function; yet, the mechanisms underpinning this relationship and the degree to which plant community structure and climate mediate the effects of plant species loss remain unclear. Here, we explored how plant species loss through experimental removal shaped belowground function in ecosystems characterized by different climatic regimes and edaphic properties. We measured plant community composition as well as potential carbon (C) and nitrogen (N) mineralization and microbial extracellular enzyme activity in soils collected from four unique plant removal experiments located along an elevational gradient in Colorado, USA. We found that, regardless of the identity of the removed species or the climate at each site, plant removal decreased the absolute variation in potential N mineralization rates and marginally reduced the magnitude of N mineralization rates. While plant species removal also marginally reduced C mineralization rates, C mineralization, unlike N mineralization, displayed sensitivity to the climatic and edaphic differences among sites, where C mineralization was greatest at the high elevation site that receives the most precipitation annually and contains the largest soil total C pool. Plant removal had little impact on soil enzyme activity. Removal effects were not contingent on the amount of biomass removed annually, and shifts in mineralization rates occurred despite only marginal shifts in plant community structure following plant species removal. Our results present a surprisingly simple and consistent pattern of belowground response to the loss of dominant plant species across an elevational gradient with different climatic and edaphic properties, suggesting a common response of belowground ecosystem function to plant species loss regardless of which plant species are lost or the broader climatic context.

Greater topoclimatic control of above‐ versus below‐ground communities - Heidi K. Mod; Daniel Scherrer; Valeria Di Cola; Olivier Broennimann; Quentin Blandenier; Frank T. Breiner; Aline Buri; Jérôme Goudet; Nicolas Guex; Enrique Lara; Edward A. D. Mitchell; Hélène Niculita‐Hirzel; et al. (Global Change Biology, 2020)
Assessing the degree to which climate explains the spatial distributions of different taxonomic and functional groups is essential for anticipating the effects of climate change on ecosystems. Most effort so far has focused on above‐ground organisms, which offer only a partial view on the response of biodiversity to environmental gradients. Here including both above‐ and below‐ground organisms, we quantified the degree of topoclimatic control on the occurrence patterns of >1,500 taxa and phylotypes along a c. 3,000 m elevation gradient, by fitting species distribution models. Higher model performances for animals and plants than for soil microbes (fungi, bacteria and protists) suggest that the direct influence of topoclimate is stronger on above‐ground species than on below‐ground microorganisms. Accordingly, direct climate change effects are predicted to be stronger for above‐ground than for below‐ground taxa, whereas factors expressing local soil microclimate and geochemistry are likely more important to explain and forecast the occurrence patterns of soil microbiota. Detailed mapping and future scenarios of soil microclimate and microhabitats, together with comparative studies of interacting and ecologically dependent above‐ and below‐ground biota, are thus needed to understand and realistically forecast the future distribution of ecosystems.

Consistently inconsistent drivers of microbial diversity and abundance at macroecological scales - John Nicholas Hendershot; Quentin D. Read; Jeremiah A. Henning; Nathan J. Sanders; Aimée T. Classen (Ecology, 2017)
Macroecology seeks to understand broad‐scale patterns in the diversity and abundance of organisms, but macroecologists typically study aboveground macroorganisms. Belowground organisms regulate numerous ecosystem functions, yet we lack understanding of what drives their diversity. Here, we examine the controls on belowground diversity along latitudinal and elevational gradients. We performed a global meta‐analysis of 325 soil communities across 20 studies conducted along temperature and soil pH gradients. Belowground taxa, whether bacterial or fungal, observed along a given gradient of temperature or soil pH were equally likely to show a linear increase, linear decrease, humped pattern, trough‐shaped pattern, or no pattern in diversity along the gradient. Land‐use intensity weakly affected the diversity‐temperature relationship, but no other factor did so. Our study highlights disparities among diversity patterns of soil microbial communities. Belowground diversity may be controlled by the associated climatic and historical contexts of particular gradients, by factors not typically measured in community‐level studies, or by processes operating at scales that do not match the temporal and spatial scales under study. Because these organisms are responsible for a suite of key processes, understanding the drivers of their distribution and diversity is fundamental to understanding the functioning of ecosystems.